What are the determinants of fuel subsidies in Asia-Pacific Economic Cooperation countries? - Nam Foo; Hooi Hooi Lean; Ruhul A. Salim (Asian Development Bank Institute (ADBI), 2020)
Fuel subsidies are widespread and debated extensively. The issues with these subsidies are fully acknowledged by many energy economists; however, the total subsidy level remains high. This is because energy subsidies are often closely related to the political economy viewpoint. Moreover, the rationale underlying fossil fuel subsidies, particularly concerning political, economic, and social contexts, is to reduce energy poverty, ensure access to energy, and redistribute the wealth that stems from the exploitation of national resources. Although there is considerable controversy surrounding the efficiency of these policies, energy subsidies confer private benefits on particular interest groups and, once implemented, tend to persist. This paper discusses and models various aspects of the political economy of fuel subsidy reform in selected Asia-Pacific Economic Cooperation (APEC) economies. Applying a panel data set from the period 1991-2018, the paper provides an empirical analysis of the economic and political perspectives of fuel prices in APEC countries resulting from the elimination of fossil fuel subsidization policies. Our findings robustly support the current economic trend of those governments that have decided to phase out fossil fuel energy policies. Based on these findings, we conclude that a range of economic, political, and social parameters systematically influence fuel prices.
Keywords: E61; Q43; Q48; 330; APEC; political economy; subsidies